General Balbo
Italian general. Caption on card: "... the arrival of General Balbo, commanding 25 planes, in an overseas flight, a gesture from Mussolini... European politics were getting tenser by the minute, but that didn't keep Mayor Kelly (white suit) from doing the honors for General Balbo."